Aceiros e estradas florestais : uma questão sobre compatibilidade econômica e de proteção - Freitas, Yasnay Maria de Moraes Massola (2020)
There is a very fine line about forest roads and firebreaks, as well as about the definition of their functions, dimensions, concepts and characteristics. The objective of this work is the bibliographic survey about this theme, definition of the concept of forest roads and firebreaks, their use and importance for Brazil, in addition to a brief overview of the fires in the country, presenting the deficiency on laws that regulate maintenance fire breaks and forest roads. Finally, it was possible to observe that most of the works used in this review are exclusive to the theme of forest roads or forest firebreaks, in isolation, and there was a need for studies that propose optimum density for firebreaks, as well as, later, a study optimized for proposing an effective optimum density for forest infrastructures that consider fire breaks and roads together.